Using different zebrafish models to explore liver regeneration - Mo, Dashuang; Lv, Mengzhu; Mao, Xiaoyu (Frontiers in Cell and Developmental Biology, 2024)
The liver possesses an impressive capability to regenerate following various injuries. Given its profound implications for the treatment of liver diseases, which afflict millions globally, liver regeneration stands as a pivotal area of digestive organ research. Zebrafish (Danio rerio) has emerged as an ideal model organism in regenerative medicine, attributed to their remarkable ability to regenerate tissues and organs, including the liver. Many fantastic studies have been performed to explore the process of liver regeneration using zebrafish, especially the extreme hepatocyte injury model. Biliary-mediated liver regeneration was first discovered in the zebrafish model and then validated in mammalian models and human patients. Considering the notable expansion of biliary epithelial cells in many end-stage liver diseases, the promotion of biliary-mediated liver regeneration might be another way to treat these refractory liver diseases. To date, a comprehensive review discussing the current advancements in zebrafish liver regeneration models is lacking. Therefore, this review aims to investigate the utility of different zebrafish models in exploring liver regeneration, highlighting the genetic and cellular insights gained and discussing the potential translational impact on human health.